The Expectations Regarding Aging and Ageism Perspective between Nurses and Caregivers in Long-term Care Facilities - Sari, Dianis Wulan; Ulfiana, Elida; Anggraini, Nourmayansa Vidya; Kristianingrum, Niko Dima; Aurizki, Gading Ekapuja; Noguchi-Watanabe, Maiko (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Ageism negatively impacts older adults’ health, especially in long-term care facilities (LTCFs), where healthcare workers often hold unfavorable views of them. Understanding these perspectives is vital for combating ageism and improving LTCF quality. Yet, comprehensive studies on healthcare workers’ attitudes toward ageism are lacking, hindering targeted interventions. Therefore, grasping their attitudes and behaviors is crucial for addressing ageism in LTCFs and enhancing care for older adults.Purpose: This study aimed to explore healthcare workers’ expectations regarding aging and their perspective on ageism towards older adults in LTCFs.Methods: This study was randomly conducted in sixteen LTCFs across Indonesia’s five largest islands using a cross-sectional study with a comparative descriptive design. Participants included 56 nurses and 173 non-licensed caregivers. Data on aging expectations and ageism perspectives during the COVID-19 pandemic were collected. An online and offline self-administered questionnaires (i.e., participant’s characteristics, the expectations regarding aging survey, ageism perspective in time of the COVID-19 pandemic) were conducted. Differences between nurses and caregivers were analyzed using chi-square and independent t-tests.Results: Altogether, 56 nurses and 173 caregivers (with an average age of 39.9 years) participated in the study. Significant differences were observed between nurses and non-licensed caregivers in their expectations regarding physical health, mental health, and overall expectations regarding aging (p-value = <0.001, <0.001, <0.001, respectively). Non-licensed caregivers had higher mean scores for each item compared to nurses. Whereas, the perspective nurse and non-licensed caregivers were significantly different about older adults being more accessible to being infected with SARS-CoV-2, vulnerable population, prone to severity, easier to expose virus, low income, must isolated (p-value = 0.029, 0.007, 0.010, 0.033, <0.001, <0.001, respectively). The mean score of each item of nurses was higher than non-licensed caregivers.Conclusion: The expectation regarding aging of caregivers was higher than nurses. In line, the nurses’ scores have a lower attitude toward ageism during time COVID-19 pandemic. Exposure to ageism behavior and ageing conditions needs to be done for healthcare workers.